2019
DOI: 10.3390/antiox9010008
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity of Gold Nanoparticles Synthesized Using Wedelolactone in RIN-5F Cell Line

Abstract: We synthesized the gold nanoparticles (AuNPs) using wedelolactone (WDL) and characterized them using UV-visible spectroscopy, fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopic (SEM), transmission electron microscopic (TEM), energy dispersive X-ray diffraction, and atomic force microscopic (AFM) studies. The electronic spectrum exhibited an absorption peak at 535 nm. The FT-IR results proved that WDL was stabilized on the surface of AuNPs by acting as a cappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…For example, studies performed on the rat insulinoma cell line INS-1 have shown that cells exposed to DEHP for 24 h at different concentrations in the micromolar range [44, 45] exhibited decreased insulin secretion. A similar response was found in the murine β-cell line Rin 5F [46]. Under in vivo conditions, DEHP has also been shown to negatively affect pancreatic β-cell function and, accordingly, glucose homeostasis [4751].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…For example, studies performed on the rat insulinoma cell line INS-1 have shown that cells exposed to DEHP for 24 h at different concentrations in the micromolar range [44, 45] exhibited decreased insulin secretion. A similar response was found in the murine β-cell line Rin 5F [46]. Under in vivo conditions, DEHP has also been shown to negatively affect pancreatic β-cell function and, accordingly, glucose homeostasis [4751].…”
Section: Discussionmentioning
confidence: 53%
“…A similar response was found in the murine -cell line Rin 5F [46]. Under in vivo conditions, DEHP has also been shown to negatively affect pancreatic -cell function and, accordingly, glucose homeostasis [47][48][49][50][51].…”
Section: Dehpmentioning
confidence: 56%
“…The treatment of di (2-ethylhexyl) phthalate plasticizer-exposed cells with nanoparticles (10, 20, 40, and 80 µmol/L) for 24 hours improved cell viability, increased secretion of insulin, decreased levels of reactive oxygen species, and restored antioxidant enzymes, indicating its ability to reduce oxidative stress, which is beneficial in the treatment of type 2 DM. 28 …”
Section: Resultsmentioning
confidence: 99%
“…The majority of synthesized nanoformulations have been evaluated in only preclinical studies, 80 primarily using cell culture models 28 and other in vitro models. 31 In addition, almost all of the studies included in this review were of only acute or subacute duration and did not attempt to elucidate anti-DM mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor Nrf2 mediates the cellular response to oxidative stress by binding to the antioxidant response element in the promoters of genes for various antioxidant proteins and enzymes such as heme oxygenase-1 (HO-1), SOD1, CAT, GPx1, and NADPH quinone dehydrogenase 1 (NQO1), and inducing their expression [ 284 ]. Nuclear factor erythroid 2-related factor 2 is regulated by binding to Kelch-like ECH-associated protein 1 (Keap1) as well as by microRNA-27a, which is redox-sensitive.…”
Section: Effects Of Nanoparticles On Insulin Calcium and Nitric Oxide...mentioning
confidence: 99%